Glass ceramic having specific thermal expansion characteristics
Patent Information
- Application Number
- JP2024207519
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-22
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-05
Smart Images

Figure 2025029015000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to glass-ceramics which exhibit specific thermal expansion behavior while at the same time exhibiting good melting, formability and ceramizability, as well as the use of the glass-ceramics according to the invention in precision components.
[0002] 2. Background of the Invention Low thermal expansion or low CTE (Coefficient of Thermal Expansion) materials and precision components are already known from the prior art.
[0003] Ceramics, Ti-doped quartz glass and glass ceramics are known as precision component materials with low thermal expansion in the temperature range around room temperature.Low thermal expansion glass ceramics are in particular lithium aluminum silicate glass ceramics (LAS glass ceramics), which are described, for example, in U.S. Pat. No. 4,851,372, U.S. Pat. No. 5,591,682, EP-A-587979, U.S. Pat. No. 7,226,881, U.S. Pat. No. 7,645,714, DE-A-102004008824, DE-A-102018111144.Another precision component material is cordierite ceramic or cordierite glass ceramic.
[0004] Such materials are often used in precision components which have to meet particularly stringent demands regarding their properties (e.g. mechanical, physical, optical properties). Such materials are used in particular in ground- and space-based astronomy and Earth observation, LCD lithography, microlithography and EUV lithography, metrology, spectroscopy and measurement engineering. In this case, components with particularly low thermal expansion are required depending on the specific application.
[0005] Generally, the thermal expansion of a material is measured by a static method in which the length of a test specimen is obtained at the start and end of a specific temperature range, and the average expansion coefficient α or CTE (Coefficient of Thermal Expansion) is calculated from the difference in length. In this case, the CTE is expressed as the average value in this temperature range, and for example, in the temperature range from 0°C to 50°C, it is expressed as CTE(0;50) or α(0;50).
[0006] In order to meet the ever-increasing demands, materials have been developed that have a CTE that is better suited to the field of use of the parts formed from them. For example, the average CTE can be optimized not only for the standard temperature interval CTE(0;50), but also for example for a temperature interval near the actual use temperature, for example 19°C-25°C, i.e. CTE(19;25) for a specific lithography application. In addition to determining the average CTE, the thermal expansion of the test specimen can also be determined in a very small temperature interval and represented as a CTE-T curve. Preferably, such a CTE-T curve can have zero crossings at one or more temperatures, preferably at or near the planned use temperature. At the zero crossings of the CTE-T curve, the relative change in length with respect to the temperature change is particularly small. For some glass ceramics, the zero crossings of such a CTE-T curve can be shifted toward the use temperature of the part by suitable temperature treatment. In addition, in order to minimize the change in length of the part even with small temperature changes, it is desirable to minimize the slope of the CTE-T curve near the use temperature in addition to the absolute value of the CTE. For these particular zero expansion glass-ceramics, the optimization of the CTE or thermal expansion is typically achieved by varying the ceramization conditions while keeping the composition the same.
[0007] A detrimental effect in known precision components and materials, in particular in glass ceramics such as LAS glass ceramics, is “thermal hysteresis”, which is hereinafter abbreviated as “hysteresis”. Hysteresis here means that the change in length of a specimen when heated at a constant heating rate differs from the change in length of the specimen when subsequently cooled at a constant cooling rate, even if the cooling and heating rates are of the same magnitude. If the change in length is plotted as a function of the heating or cooling temperature, a classic hysteresis curve is obtained. The shape of the hysteresis curve also depends on the rate of temperature change. The faster the temperature change, the more pronounced the hysteresis effect. Due to the hysteresis effect, it is clear that the thermal expansion of LAS glass ceramics depends on temperature and time, i.e. for example on the rate of temperature change, which has already been shown, for example, in O. Lindig und W. Pannhorst, “Thermal expansion and length stability of ZERODUR (R) in dependence on temperature and time”, APPLIED OPTICS, Vol. 24, No. 20, Okt. 1985; R. Haug et al., “Length variation in ZERODUR (R) 1989; R. Jedamzik et al., “Modeling of the thermal expansion behavior of ZERODUR (R)at arbitrary temperature profiles”, Proc. SPIE Vol. 7739, 2010; DB Hall, “Dimensional stability tests over time and temperature for several low-expansion glass ceramics”, APPLIED OPTICS, Vol. 35, No. 10, April 1996.
[0008] Glass-ceramics that exhibit thermal hysteresis undergo length changes that are slower or faster than the temperature change, so that the material or precision components manufactured therefrom exhibit disruptive isothermal length changes, i.e. even when the temperature is kept constant after a temperature change (so-called "isothermal hold"), the material still undergoes length changes until a steady state is reached. If the material is then heated and cooled again, the same effect appears again.
[0009] In previously known LAS glass-ceramics, it has not been possible to eliminate the thermal hysteresis effect by varying the ceramization conditions for the same composition without affecting other properties.
[0010] With regard to the properties of materials used in precision components, especially glass ceramics, the temperature range 0 ° C to 50 ° C, especially 10 ° C to 35 ° C or 19 ° C to 25 ° C, is often relevant, where a temperature of 22 ° C is usually referred to as room temperature. Since precision components are often used in the temperature range from 0 ° C to room temperature, materials that exhibit thermal hysteresis effects or isothermal length changes are disadvantageous, since they can cause optical disturbances in optical components, for example lithography mirrors or astronomical or space mirrors. In other glass ceramic precision components used in metrology (e.g. precision measuring instruments, reference plates in interferometers), they can cause measurement errors.
[0011] Several known materials, such as ceramics, Ti-doped fused silica, and certain glass-ceramics, have an average coefficient of thermal expansion (CTE(0;50)) of 0±0.1×10 -6 / K (corresponding to 0±0.1 ppm / K). Materials with such a low average CTE in the aforementioned temperature range are called zero expansion materials in the sense of the present invention. However, such glass-ceramics, especially LAS glass-ceramics, with optimized average CTE generally exhibit thermal hysteresis in the temperature range of 10° C. to 35° C. That is, in particular when used around room temperature (i.e. 22° C.), these materials suffer from detrimental hysteresis effects that impair the accuracy of precision parts manufactured with them. For this reason, glass-ceramic materials that do not show significant hysteresis at room temperature have been developed (see US Pat. No. 4,851,372), but the effect has not disappeared, but has simply been shifted to the lower temperature side, so that these glass-ceramics still show a pronounced hysteresis that can be detrimental at temperatures below 10° C. Therefore, in order to characterize the thermal hysteresis of a material in a given temperature range, the present invention considers the thermal behavior of the material for different temperature points within this range. Although some glass-ceramics do not exhibit significant hysteresis at 22° C. and 5° C., these glass-ceramics have an average CTE(0;50) >0±0.1 ppm / K and are not zero expansion glass-ceramics as defined above.
[0012] Further demands on glass-ceramic materials are good meltability of the glass components as well as easy melt control and homogenization of the base glass melt in industrial production plants to allow successful ceramization of the glass and subsequently meet the high demands imposed on the glass-ceramic with regard to CTE uniformity, internal quality, especially low inclusions (especially bubbles), low streak levels, and polishability.
[0013] It was therefore an object of the present invention to provide a glass ceramic which exhibits improved expansion behavior.A further object of the present invention was to provide an industrially producible glass ceramic which has zero expansion and low thermal hysteresis, in particular in the temperature range from 10° C. to 35° C., and precision components manufactured from said material.
[0014] The above-mentioned problems are solved by the subject matter described in the claims. The invention has various aspects: According to one aspect of the present invention, there is provided a LAS glass ceramic having an average coefficient of thermal expansion (CTE) of at most 0±0.1×10 in the range of 0 to 50° C. -6 / K, has a thermal hysteresis of <0.1 ppm over the temperature range of at least 10°C to 35°C, and contains the following components (in mole % on an oxide basis): [Table 1] At least one component selected from the group consisting of P2O5, R2O, and RO, where R2O may be Na2O and / or K2O and / or Cs2O and / or Rb2O, and RO may be CaO and / or BaO and / or SrO. A nucleating agent having a content of 1.5 to 6 mol %, the nucleating agent being TiO 2、 ZrO 2、 A nucleating agent, which is at least one component selected from the group consisting of Ta2O5, Nb2O5, SnO2, MoO3, and WO3.
[0023] A LAS glass-ceramic is provided, comprising:
[0015] According to a further aspect of the invention, the invention relates to the use of the glass ceramic according to the invention as a substrate for precision components.
[0016] According to a further aspect of the invention, the invention relates to the use of the LAS glass ceramic according to the invention in precision components, in particular in precision components for use in metrology, spectroscopy, measurement engineering, lithography, astronomy or Earth observation from outer space, for example as mirrors or mirror supports for segmented or monolithic astronomical telescopes or as light or ultralight mirror substrates, for example for space-based telescopes or as high-precision structural components, for example for distance measurements in outer space or optical components for Earth observation, as precision components such as standards, precision measuring instruments, reference plates for interferometers for precision metrology, for example as mechanical precision components for ring laser gyroscopes, clockwork springs, as mirrors and prisms, for example in LCD lithography, as mask holders, wafer tables, reference plates, reference frames and grid plates, for example in microlithography and EUV (Extreme UV) microlithography where reflective optics are used, and also as mirrors and / or photomask substrates or reticle mask blanks in EUV microlithography.
[0017] According to another aspect, the invention relates to a precision component comprising the LAS glass ceramic according to the invention. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 shows the CTE-T curves of low linear thermal expansion materials, e.g. for precision components, known from the prior art. [Diagram 2] Figure 1 shows the hysteresis behavior of three glass-ceramic samples, determined by the same method used in the present invention, taken from R. Jedamzik et al., “Modeling of the thermal expansion behavior of ZERODUR(R) at arbitrary temperature profiles”, Proc. SPIE Vol. 7739, 2010. [Diagram 3]FIG. 1 shows hysteresis curves (dashed line = cooling curve, dotted line = heating curve) for known glass-ceramic materials that can be used to manufacture precision components and have a thermal hysteresis of >0.1 ppm over a temperature range of at least 10° C. to 35° C. [Figure 4] FIG. 1 shows hysteresis curves (dashed line = cooling curve, dotted line = heating curve) for known glass-ceramic materials that can be used to manufacture precision components and have a thermal hysteresis of >0.1 ppm over a temperature range of at least 10° C. to 35° C. [Diagram 5] FIG. 1 shows hysteresis curves (dashed line = cooling curve, dotted line = heating curve) for known glass-ceramic materials that can be used to manufacture precision components and have a thermal hysteresis of >0.1 ppm over a temperature range of at least 10° C. to 35° C. [Figure 6] FIG. 1 shows hysteresis curves (dashed line = cooling curve, dotted line = heating curve) for known glass-ceramic materials that can be used to manufacture precision components and have a thermal hysteresis of >0.1 ppm over a temperature range of at least 10° C. to 35° C. [Figure 7] FIG. 1 shows hysteresis curves (dashed line = cooling curve, dotted line = heating curve) for known glass-ceramic materials that can be used to manufacture precision components and have a thermal hysteresis of >0.1 ppm over a temperature range of at least 10° C. to 35° C. [Figure 8] FIG. 1 shows hysteresis curves (dashed line = cooling curve, dotted line = heating curve) for known glass-ceramic materials that can be used to manufacture precision components and have a thermal hysteresis of >0.1 ppm over a temperature range of at least 10° C. to 35° C. [Figure 9] FIG. 1 shows the hysteresis curve (dashed line = cooling curve, dotted line = heating curve) of a prior art glass-ceramic that can be used to manufacture precision components and has a thermal hysteresis of <0.1 ppm at least in the temperature range from 10°C to 35°C, but the steepness of the curve makes it clear that this glass-ceramic is not zero expansion. [Figure 10]FIG. 1 shows a hysteresis curve (dashed line = cooling curve, dotted line = heating curve) of a glass ceramic according to the invention (composition according to Example 6 in Table 1) that can be used for the manufacture of precision components according to the invention and has a thermal hysteresis of <0.1 ppm in the temperature range of at least 10° C. to 35° C. [Figure 11] FIG. 1 shows a hysteresis curve (dashed line = cooling curve, dotted line = heating curve) of a glass ceramic according to the invention (composition according to Example 7 in Table 1) that can be used for the manufacture of precision components according to the invention and has a thermal hysteresis of <0.1 ppm in the temperature range of at least 10 ° C. to 35 ° C. [Figure 12] FIG. 1 shows a normalized Δl / l0-T curve (also called dl / l0 curve) of a glass ceramic according to the invention (composition according to Example 6 in Table 1) and an auxiliary line for determining the parameter F as an index of flatness of the expansion curve in the temperature range from 0° C. to 50° C. [Figure 13] FIG. 1 shows a normalized Δl / l0-T curve (also called dl / l0 curve) of a glass ceramic according to the invention (composition according to Example 7 in Table 1) and an auxiliary line for determining the parameter F as an index of flatness of the expansion curve in the temperature range from 0° C. to 50° C. [Figure 14] FIG. 1 shows a normalized Δl / l0-T curve of a known material that can be used to manufacture a known precision part, and an auxiliary line for determining the parameter F as an index of flatness of the expansion curve in the temperature range from -10°C to 70°C. [Figure 15] FIG. 1 shows a normalized Δl / l0-T curve of a known material that can be used to manufacture a known precision part, and an auxiliary line for determining the parameter F as an index of flatness of the expansion curve in the temperature range from -10°C to 80°C. [Figure 16] FIG. 1 shows a normalized Δl / l0-T curve of a known material that can be used to manufacture a known precision part, and an auxiliary line for determining the parameter F as an index of flatness of the expansion curve in the temperature range from -20°C to 80°C. [Figure 17]FIG. 1 shows a normalized Δl / l0-T curve of a known material that can be used to manufacture a known precision part, and an auxiliary line for determining the parameter F as an index of flatness of the expansion curve in the temperature range from -10°C to 70°C. [Figure 18] FIG. 14 shows normalized Δl / l0-T curves for the glass-ceramics of FIGS. 12 and 13 in the temperature range of −30° C. to +70° C. [Figure 19] A diagram showing normalized Δl / l0-T curves for known materials in the temperature range of -30°C to +70°C. [Figure 20] FIG. 13 shows that the CTE-T curve of the glass-ceramic of FIG. 12, which can be used to manufacture advantageous precision components, advantageously exhibits a CTE plateau. [Figure 21] FIG. 14 shows that the CTE-T curve of the glass-ceramic of FIG. 13, which can be used to manufacture advantageous precision components, advantageously exhibits a CTE plateau. [Figure 22] FIG. 25 is a graph showing the slope of the CTE-T curve in FIG. 24. [Diagram 23] FIG. 26 shows the slope of the CTE-T curve in FIG. 25. [Figure 24] FIG. 13 shows a graph of different CTEs for two embodiments of the present invention tuned by different ceramization parameters. [Diagram 25] FIG. 13 shows a graph of different CTEs for two embodiments of the present invention tuned by different ceramization parameters. [Figure 26] FIG. 2 shows the slope of the CTE-T curve for a glass ceramic according to the present invention having a composition according to Example 17 of Table 1. [Figure 27] FIG. 1 shows the normalized Δl / l0-T curve of a glass ceramic according to the invention (composition according to Example 17 of Table 1) and an auxiliary line for determining the alternative parameter f(20;40) as an index of the flatness of the expansion curve in the temperature range from 20° C. to 40° C. [Figure 28] FIG. 14 shows the normalized Δl / l0-T curve of the glass-ceramic of FIG. 13 and an auxiliary line for determining the alternative parameter f(-10;30) as an index of the flatness of the expansion curve in the temperature range from -10°C to 30°C. [Figure 29] FIG. 14 shows the normalized Δl / l0-T curve of the glass-ceramic of FIG. 13 and an auxiliary line for determining the alternative parameter f(20;70) as an index of the flatness of the expansion curve in the temperature range from 20° C. to 70° C. [Diagram 30] FIG. 1 shows the normalized Δl / l0-T curve of a glass ceramic according to the invention (composition according to Example 14 of Table 1) and an auxiliary line for determining the alternative parameter f(-10;30) as an indicator of the flatness of the expansion curve in the temperature range from -10° C. to 30° C.
[0019] The subject of the invention is a LAS glass ceramic having an average coefficient of thermal expansion CTE in the range 0-50 °C of at most 0 ± 0.1 × 10 -6 / K, has a thermal hysteresis of <0.1 ppm over the temperature range of at least 10°C to 35°C, and contains the following components (in mole % on an oxide basis): [Table 2] At least one component selected from the group consisting of P2O5, R2O, and RO, where R2O may be Na2O and / or K2O and / or Cs2O and / or Rb2O, and RO may be CaO and / or BaO and / or SrO. A nucleating agent having a content of 1.5 to 6 mol %, the nucleating agent being TiO 2、 ZrO 2、 A nucleating agent, which is at least one component selected from the group consisting of Ta2O5, Nb2O5, SnO2, MoO3, and WO3. and LAS glass-ceramics, including
[0020] The present invention provides for the first time an LAS glass ceramic (hereinafter also referred to as glass ceramic) that combines several important properties: the average thermal expansion coefficient CTE in the range of 0 to 50° C. is at most 0±0.1×10 -6 / K, i.e. the LAS glass ceramic has zero expansion. Furthermore, the LAS glass ceramic has a thermal hysteresis of <0.1 ppm at least in the temperature range from 10° C. to 35° C. Materials with such low hysteresis effects of <0.1 ppm in the abovementioned temperature range are hereinafter referred to as “hysteresis-free”. The statement of hysteresis depends on the rate of temperature change used for the measurement, as already mentioned above, so that in the present invention the statement of hysteresis relates to a heating / cooling rate of 36 K / h, i.e. 0.6 K / min. In an advantageous embodiment, the LAS glass ceramic can be hysteresis-free at least in the temperature range from 5° C. to 35° C., or at least in the temperature range from 5° C. to 40° C., advantageously at least in the temperature range from >0° C. to 45° C., preferably at least in the temperature range from −5° C. to 50° C.
[0021] The parameters of CTE and thermal hysteresis are explained in more detail below.
[0022] According to the invention, glass ceramics are understood to be non-porous inorganic materials having a crystalline phase and a glass phase, the matrix, i.e. the continuous phase, being usually the glass phase. To produce glass ceramics, the components of the glass ceramic are first mixed, melted and refined to cast a so-called green glass. After cooling, the green glass is crystallized in a controlled manner by reheating (so-called "controlled volume crystallization"). The green glass and the glass ceramic produced therefrom have the same chemical composition (analytical values), only the internal structure of the material is changed by ceramization. Therefore, when the composition of the "glass ceramic" is mentioned below, what is said also applies to the precursor of the glass ceramic, i.e. the green glass.
[0023] The inventors have now found for the first time that, since both components MgO and ZnO promote the development of thermal hysteresis in the temperature range of interest, it is essential to limit the contents of MgO and ZnO, as claimed, in order to provide a zero-expansion LAS glass-ceramic that is hysteresis-free at least in the temperature range of 10° C. to 35° C. In contrast, it has previously been assumed that these glass components, in combination or individually, are necessary to achieve zero expansion, particularly in zero-expansion LAS glass-ceramics, and to make the graph of the CTE-T curve of the material "flat", i.e., to reduce the slope of the CTE-T curve in the temperature range. Thus, there is a trade-off between an LAS glass-ceramic being either zero expansion or hysteresis-free.
[0024] This trade-off is eliminated according to the present invention not only by substantially omitting the use of MgO and ZnO, but also by selecting the contents of SiO2 and Li2O within the ranges specified by the present invention. It has been found in the present invention that the ranges given by the contents of SiO2 (60-71 mol%) and Li2O (7-9.4 mol%) surprisingly result in glass-ceramics that are zero expansion and hysteresis-free.
[0025] The LAS glass ceramic comprises a negatively expanding crystalline phase, which contains or consists of a high-quartz solid solution, also called β-eucryptite, advantageously in the present invention, and a positively expanding glassy phase. In addition to SiO2 and Al2O3, Li2O is also a major component of the solid solution. Also, ZnO and / or MgO, if present, are likewise incorporated in the solid solution phase and affect, together with Li2O, the expansion behavior of the crystalline phase. This means that the above-mentioned provisions according to the invention (reduction, preferably elimination, of MgO and ZnO) have a significant influence on the type and properties of the solid solution formed during ceramization. In contrast to known zero-expansion glass-ceramics, in which inter alia MgO and ZnO are used to adjust the desired expansion behavior of the glass-ceramic, the present invention uses for this purpose at least one component selected from the group consisting of P2O5, R2O and RO, where R2O can be Na2O and / or K2O and / or Rb2O and / or Cs2O and RO can be CaO and / or BaO and / or SrO. Besides MgO and ZnO, the aforementioned alkaline earth metal oxides and alkali metal oxides remain, if present, but they remain in the glass phase and are not incorporated into the high-quartz solid solution.
[0026] In the present invention, it has been found that it can be advantageous to provide a zero-expansion and hysteresis-free glass-ceramic if the composition satisfies the condition: mole fraction of SiO2 + (5 x mole fraction of Li2O) ≥ 106 or preferably ≥ 106.5, preferably mole fraction of SiO2 + (5 x mole fraction of Li2O) ≥ 107 or ≥ 107.5. Alternatively or additionally, advantageous upper limits for this condition "molar fraction of SiO2 + (5 x mole fraction of Li2O)" are ≤ 115.5, ≤ 114.5, or ≤ 113.5.
[0027] In an advantageous development, the glass ceramic can comprise the following components in molar percentages, alone or in any combination: Al2O310~22 P2O50~6 MgO 0~0.35 ZnO 0~0.5 R2O 0~6 RO 0~6 TiO2+ZrO21.5~6
[0028] In an advantageous development, the glass ceramic can comprise the following components in molar percentages, alone or in any combination: Al2O310~22 P2O50~6 MgO 0~0.3 ZnO 0~0.4 R2O 0~6 RO 0~6 TiO2+ZrO21.5~6
[0029] More preferably, the following components may be present in the glass ceramic, either alone or in any combination, in mole percent, within the abovementioned limits for R2O, RO and the sum of TiO2 + ZrO2: Na2O 0~3 K2O 0~3 Cs2O 0~2 Rb2O 0~2 CaO 0~5 BaO 0~4 SrO 0~3 TiO20~5 ZrO20~3
[0030] In an advantageous embodiment, the LAS glass ceramic comprises (in mole % on an oxide basis): Al2O310~22 P2O50~6 MgO 0~0.35 ZnO 0~0.5 R2O 0~6 RO 0~6 Nucleating agent 1.5~6 wherein the nucleating agent is preferably TiO2 and / or ZrO2.
[0031] In an advantageous embodiment, the LAS glass ceramic comprises (in mole % on an oxide basis): Al2O310~22 P2O50~6 MgO 0~0.3 ZnO 0~0.4 R2O 0~6 RO 0~6 Nucleating agent 1.5~6 wherein the nucleating agent is preferably TiO2 and / or ZrO2.
[0032] In a further advantageous embodiment, the LAS glass ceramic comprises (in mole % on an oxide basis): SiO260.50~69 Li2O 8~9.4 Al2O311~21 P2O50.5~6 MgO 0~0.2 ZnO 0~0.3 R2O 0~4 RO 0.2~4.5 Nucleating agent 2.5~5 wherein the nucleating agent is preferably TiO2 and / or ZrO2.
[0033] The glass ceramic comprises a proportion of silicon dioxide (SiO2) of at least 60 mol%, more preferably at least 60.5 mol%, also preferably at least 61 mol%, also preferably at least 61.5 mol%, even more preferably at least 62.0 mol%. The proportion of SiO2 is at most 71 mol% or less than 71 mol%, more preferably at most 70 mol% or less than 70 mol%, even more preferably at most 69 mol%, also preferably at most 68.5 mol%. A high proportion of SiO2 can lead to difficulties in melting the batch and to high melt viscosity, which can lead to problems with melt homogenization in industrial production plants. It is therefore advisable not to exceed a content of 71 mol%, preferably 70 mol%. A high melt viscosity leads to a high melt processing temperature Va. Very high temperatures are required for melt clarification and homogenization, which results in the attack of the internal surfaces of the melting unit due to the aggressiveness of the melt, which increases with temperature. Moreover, even higher temperatures may not be sufficient to produce a homogeneous melt, so that the green glass may contain streaks and inclusions (especially bubbles and particles coming from the inner surfaces of the melting unit), so that after ceramization the requirements for homogeneity of the properties of the produced glass-ceramic, for example the uniformity of the thermal expansion coefficient, are not met. For this reason, a SiO2 content lower than the stated upper limit may be preferred.
[0034] The content of Al2O3 is advantageously at least 10 mol%, preferably at least 11 mol%, preferably at least 12 mol%, more preferably at least 13 mol%, also preferably at least 14 mol%, also preferably at least 14.5 mol%, and even more preferably at least 15 mol%. If the content is too low, the low expansion solid solution is not formed or is formed in too small an amount. The proportion of Al2O3 is advantageously at most 22 mol%, preferably at most 21 mol%, preferably at most 20 mol%, even more preferably at most 19.0 mol%, and even more preferably at most 18.5 mol%. If the content of Al2O3 is too high, the viscosity increases and the disordered devitrification of the material is promoted.
[0035] The glass ceramic according to the invention may contain 0-6 mol% P2O5. The content of phosphate P2O5 in the glass ceramic may advantageously be at least 0.1 mol%, preferably at least 0.3 mol%, preferably at least 0.5 mol%, also preferably at least 0.6 mol%, more preferably at least 0.7 mol%, even more preferably at least 0.8 mol%. P2O5 is essentially incorporated into the crystalline phase of the glass ceramic and has a positive effect on the expansion behavior of the crystalline phase and thus of the glass ceramic. Furthermore, the melting of the components and the clarification behavior of the melt are improved. However, if the content of P2O5 is too high, the graph of the CTE-T curve in the temperature range 0 ° C to 50 ° C does not show the advantageous flat course. Therefore, advantageously, at most 6 mol%, preferably at most 5 mol%, more preferably at most 4 mol%, even more preferably less than 4 mol% P2O5 is contained in the glass ceramic. According to some embodiments, the glass ceramic may be free of P2O5.
[0036] In the present invention, the components SiO2, Al2O3 and / or P2O5, i.e., specific sums and ratios of components forming a high quartz solid solution, may contribute to the formation of a glass-ceramic according to the present invention.
[0037] The total proportion in mol % of the LAS glass-ceramic basic components SiO2 and Al2O3 is advantageously at least 75 mol %, preferably at least 78 mol %, preferably at least 79 mol %, more preferably at least 80 mol % and / or preferably at most 90 mol %, preferably at most 87 mol %, preferably at most 86 mol %, more preferably at most 85 mol %. If this sum is too high, the viscosity curve of the melt is shifted towards higher temperatures, which is disadvantageous as already explained in connection with the SiO2 component. If this sum is too low, too little solid solution is formed.
[0038] The total proportion in mol % of the LAS glass-ceramic basic components SiO2, Al2O3 and P2O5 is preferably at least 77 mol %, advantageously at least 81 mol %, advantageously at least 83 mol %, more preferably at least 84 mol % and / or preferably at most 91 mol %, advantageously at most 89 mol %, more preferably at most 87 mol % and according to one variant at most 86 mol %.
[0039] The ratio in molar % of P2O5 to SiO2 is preferably at least 0.005, advantageously at least 0.01, preferably at least 0.012 and / or preferably at most 0.1, more preferably at most 0.08 and according to one variant at most 0.07.
[0040] As a further component, the glass ceramic comprises lithium oxide (Li2O) in a proportion of at least 7 mol%, advantageously at least 7.5 mol%, preferably at least 8 mol%, particularly preferably at least 8.25 mol%. The proportion of Li2O is limited to at most 9.4 mol%, more preferably at most 9.35 mol%, even more preferably at most 9.3 mol% or less. Li2O is a component of the solid solution phase and contributes significantly to the thermal expansion of the glass ceramic. It is undesirable to exceed the above-mentioned upper limit of 9.4 mol%, because otherwise a glass ceramic with a negative coefficient of thermal expansion CTE (0;50) would be produced. If the Li2O content is less than 7 mol%, the amount of solid solution formed is too small and the CTE of the glass ceramic remains positive.
[0041] The glass ceramic may contain at least one alkaline earth metal oxide selected from the group consisting of CaO, BaO, SrO, which group is collectively referred to as "RO". The components of the group RO remain substantially in the amorphous glass phase of the glass ceramic and may be important for maintaining the zero expansion of the ceramized material. If the sum of CaO+BaO+SrO is too high, the CTE(0;50) aimed for according to the invention is not achieved. The proportion of RO is therefore advantageously at most 6 mol%, or at most 5.5 mol%, preferably at most 5 mol%, advantageously at most 4.5 mol%, preferably at most 4 mol%, preferably at most 3.8 mol%, even more preferably at most 3.5 mol% and also preferably at most 3.2 mol%. If the glass ceramic contains RO, an advantageous lower limit may be at least 0.1 mol%, advantageously at least 0.2 mol%, preferably at least 0.3 mol% and also preferably at least 0.4 mol%. According to some embodiments, the glass-ceramic may be free of RO.
[0042] The proportion of CaO can be preferably at most 5 mol%, advantageously at most 4 mol%, advantageously at most 3.5 mol%, advantageously at most 3 mol%, further preferably at most 2.8 mol%, more preferably at most 2.6 mol%. The glass ceramic can advantageously contain at least 0.1 mol%, advantageously at least 0.2 mol%, preferably at least 0.4 mol%, preferably at least 0.5 mol% of CaO. The glass ceramic can advantageously contain the component BaO, which is a good glass former, in a proportion of at least 0.1 mol%, preferably at least 0.2 mol% and / or at most 4 mol%, advantageously at most 3 mol%, advantageously at most 2.5 mol%, preferably at most 2 mol%, preferably at most 1.5 mol% and also preferably at most 1.4 mol%. The glass ceramic may contain at most 3 mol %, advantageously at most 2 mol %, preferably at most 1.5 mol %, preferably at most 1.3 mol %, preferably at most 1.1 mol %, more preferably at most 1 mol %, also preferably at most 0.9 mol %, and / or preferably at least 0.1 mol % of SrO. According to some embodiments, the glass ceramic does not contain CaO and / or BaO and / or SrO.
[0043] The glass ceramic optionally contains sodium oxide (Na2O) and / or potassium oxide (K2O) and / or cesium oxide (Cs2O) and / or rubidium oxide (Rb2O), i.e. Na2O-free and / or K2O-free and / or Cs2O-free and / or Rb2O-free variants are possible. The proportion of Na2O may advantageously be at most 3 mol%, preferably at most 2 mol%, preferably at most 1.7 mol%, preferably at most 1.5 mol%, preferably at most 1.3 mol%, preferably at most 1.1 mol%. The proportion of K2O may advantageously be at most 3 mol%, preferably at most 2.5 mol%, preferably at most 2 mol%, preferably at most 1.8 mol%, preferably at most 1.7 mol%. The proportion of Cs2O may advantageously be at most 2 mol%, preferably at most 1.5 mol%, preferably at most 1 mol%, preferably at most 0.6 mol%. The proportion of Rb2O may advantageously be at most 2 mol%, preferably at most 1.5 mol%, preferably at most 1 mol%, preferably at most 0.6 mol%. According to some embodiments, the glass ceramic does not comprise Na2O and / or KO and / or Cs2O and / or Rb2O.
[0044] Na2O, K2O, Cs2O, Rb2O may each be present in the glass-ceramic independently of one another in a proportion of at least 0.1 mol %, preferably at least 0.2 mol %, more preferably at least 0.5 mol %. The Na2O, K2O, Cs2O and Rb2O components remain essentially in the amorphous glass phase of the glass-ceramic and may be important in maintaining the zero expansion properties of the ceramized material.
[0045] Thus, the sum R2O of the contents Na2O, K2O, Cs2O and Rb2O may advantageously be at least 0.1 mol%, preferably at least 0.2 mol%, advantageously at least 0.3 mol%, preferably at least 0.4 mol%. A low R2O content, advantageously at least 0.2 mol%, may contribute to extending the temperature range in which the expansion curve of the glass ceramic exhibits a flat progression. The sum R2O of the contents Na2O, K2O, Cs2O and Rb2O may advantageously be at most 6 mol%, preferably at most 5 mol%, preferably at most 4 mol%, preferably at most 3 mol%, preferably at most 2.5 mol%. If the sum Na2O+K2O+Cs2O+Rb2O is too low or too high, the CTE(0;50) aimed for according to the invention may not be achieved. According to some embodiments, the glass ceramic may be free of R2O.
[0046] The glass ceramic may contain up to 0.35 mol % magnesium oxide (MgO). Further advantageous upper limits may be up to 0.3 mol %, up to 0.25 mol %, up to 0.2 mol %, up to 0.15 mol %, up to 0.1 mol %, or up to 0.05 mol %. Particularly preferably, the glass ceramic according to the invention does not contain MgO. As mentioned above, the component MgO contained in the glass ceramic causes thermal hysteresis in the temperature range from 0° C. to 50° C. The less MgO contained in the glass ceramic, the smaller the hysteresis in the aforementioned temperature range.
[0047] The glass ceramic may contain up to 0.5 mol % zinc oxide (ZnO). Further advantageous upper limits may be up to 0.45 mol %, up to 0.4 mol %, up to 0.35 mol %, up to 0.3 mol %, up to 0.25 mol %, up to 0.2 mol %, up to 0.15 mol %, up to 0.1 mol %, or up to 0.05 mol %. Particularly preferably, the glass ceramic according to the invention does not contain ZnO. As mentioned above as the inventor's knowledge, the component ZnO contained in the glass ceramic causes thermal hysteresis in the temperature range from 0 ° C to 50 ° C. The less ZnO contained in the glass ceramic, the smaller the hysteresis in the aforementioned temperature range.
[0048] With regard to the hysteresis-free nature of the glass ceramic according to the invention, it is important to fulfill the condition that MgO+ZnO is less than 0.6 mol %. Further advantageous upper limits for the sum of MgO+ZnO can be at most 0.55 mol %, at most 0.5 mol % or less than 0.5 mol %, at most 0.45 mol %, at most 0.4 mol %, at most 0.35 mol %, at most 0.3 mol %, at most 0.25 mol %, at most 0.2 mol %, at most 0.15 mol %, at most 0.1 mol %, or at most 0.05 mol %.
[0049] The glass ceramic further comprises at least one crystal nucleating agent selected from the group consisting of TiO2, ZrO2, Ta2O5, Nb2O5, SnO2, MoO3, WO3. The nucleating agent may be a combination of two or more of the abovementioned components. Another advantageous nucleating agent may be HfO2. Thus, in an advantageous embodiment, the glass ceramic comprises HfO2 and at least one crystal nucleating agent selected from the group consisting of TiO2, ZrO2, Ta2O5, Nb2O5, SnO2, MoO3, WO3. The total proportion of the nucleating agents is preferably at least 1.5 mol%, preferably at least 2 mol% or more than 2 mol%, more preferably at least 2.5 mol% and according to a particular variant at least 3 mol%. The upper limit may be at most 6 mol%, preferably at most 5 mol%, preferably at most 4.5 mol% or at most 4 mol%. In a particularly advantageous variant, the abovementioned upper and lower limits apply to the sum of TiO2 and ZrO2.
[0050] The glass ceramic can preferably contain titanium oxide (TiO2) in a proportion of at least 0.1 mol%, advantageously at least 0.5 mol%, preferably at least 1.0 mol%, preferably at least 1.5 mol%, preferably at least 1.8 mol% and / or preferably at most 5 mol%, advantageously at most 4 mol%, more preferably at most 3 mol%, even more preferably at most 2.5 mol%, preferably at most 2.3 mol%. TiO2-free variants of the glass ceramic according to the invention are possible.
[0051] The glass ceramic can advantageously further comprise zirconium oxide (ZrO2) in a proportion of at most 3 mol%, preferably at most 2.5 mol%, more preferably at most 2 mol%, preferably at most 1.5 mol% or at most 1.2 mol%. Preferably, ZrO2 is present in a proportion of at least 0.1 mol%, more preferably at least 0.5 mol%, at least 0.8 mol% or at least 1.0 mol%. ZrO2-free variants of the glass ceramic according to the invention are possible.
[0052] According to some advantageous variants of the invention, 0-5 mol% of Ta2O5 and / or Nb2O5 and / or SnO2 and / or MoO3 and / or WO3 may be included in the glass ceramic, individually or in total, and these may serve, for example, as alternative or additional nucleating agents or for adjusting optical properties, for example the refractive index. HfO2 may also be an alternative or additional nucleating agent. To adjust the optical properties, in some advantageous variants, for example Gd2O3, Y2O3, HfO2, Bi2O3 and / or GeO2 may be included.
[0053] Glass ceramics are As2O3, Sb2O3, SnO2, SO4 2- , F - , Cl - , Br - or mixtures thereof, in a proportion of more than 0.05 mol %, or at least 0.1 mol % and / or at most 1 mol %, however, fluorine as a fining agent may reduce the transparency of the glass-ceramic, so that if this component is present, it is preferably limited to a maximum of 0.5 mol %, preferably a maximum of 0.3 mol %, preferably a maximum of 0.1 mol %. Preferably, the glass-ceramic is fluorine-free.
[0054] The above mentioned glass compositions can optionally contain additives of colouring oxides, such as, for example, Nd2O3, Fe2O3, CoO, NiO, V2O5, MnO2, CuO, CeO2, Cr2O3, rare earth oxides, each individually or in total in a content of 0 to 3 mol %. A preferred variant is one which does not contain any colouring oxides.
[0055] B2O3 can have a detrimental effect on the transparency of the glass ceramic. Therefore, in an advantageous variant, the content of this component is limited to <0.2 mol %, preferably at most 0.1 mol %. A preferred variant is one that is free of B2O3.
[0056] According to an advantageous embodiment of the invention, the composition does not comprise any ingredients not mentioned above.
[0057] According to an advantageous embodiment of the invention, the glass ceramic or green glass according to the invention preferably consists to at least 90 mol %, more preferably at least 95 mol %, most preferably at least 99 mol % of the above-mentioned components, or preferably of the components SiO2, Al2O3, Li2O, PO5, R2O, RO and nucleating agents.
[0058] According to an advantageous development of the glass ceramic, the glass ceramic is substantially free of one or more glass components selected from the group consisting of MgO, ZnO, PbO, B2O3, CrO3, F, Cd compounds.
[0059] According to the invention, the expression "free of X" or "free of component X" means that the glass-ceramic is substantially free of this component X, i.e. such component is at most only present as an impurity in the glass and is not added to the composition as a single component. With regard to impurities, in particular MgO and / or ZnO, in the MgO-free and / or ZnO-free variants, the limit of 0.03 mol %, preferably 0.01 mol %, respectively, for the single components, should not be exceeded. For the other glass components, higher impurity contents may be possible, up to 0.1 mol %, preferably up to 0.05 mol %, advantageously up to 0.01 mol %, advantageously up to 0.005 mol %, advantageously up to 0.003 mol %, for some components, respectively, for one component. Here, X stands for any component, for example PbO.
[0060] The glass ceramic according to the invention has a high-quartz solid solution as the predominant crystalline phase. The predominant crystalline phase is the crystalline phase with the highest volume percentage among the crystalline phases. The high-quartz solid solution is a metastable phase that can change composition and / or structure or transform into other crystalline phases depending on the crystallization conditions. The high-quartz containing solid solution has very low thermal expansion or even decreases with increasing temperature. In an advantageous embodiment, the crystalline phase does not include β-spodumene and keatite.
[0061] Advantageous embodiments of the LAS glass ceramic have a crystalline phase proportion of less than 70% by volume and / or advantageously more than 45% by volume. The crystalline phase consists of a high-quartz solid solution, also called β-eucryptite solid solution. The average crystallite size of the high-quartz solid solution is advantageously <100 nm, preferably <80 nm, preferably <70 nm. Due to the small crystallite size, the glass ceramic is transparent and can also be polished better. In an advantageous variant, the average crystallite size of the high-quartz solid solution can be ≦60 nm, preferably ≦50 nm. The crystalline phases, their proportions and the average crystallite size are determined by X-ray diffraction analysis as known per se.
[0062] According to one embodiment of the present invention, transparent glass ceramics are produced. Due to the transparency, many properties of such glass ceramics can be better evaluated, in particular of course the internal quality. The glass ceramics according to the invention are transparent, i.e. have a net transmission of at least 70% in the wavelength range from 350 to 650 nm. A high content of B2O3 and / or fluorine can reduce the transparency. An advantageous variant therefore does not contain one or both of the aforementioned components. Furthermore, the glass ceramics produced according to the present invention are non-porous and crack-free. In the present invention, "non-porous" means that the porosity is less than 1%, preferably less than 0.5%, more preferably less than 0.1%. Cracks are gaps in a continuous structure, i.e. discontinuities.
[0063] To be able to produce homogeneous glass ceramics in industrial production plants, it is advantageous if the processing temperature Va of the green glass on which the glass ceramic is based (and thus of the glass ceramic) is advantageously at most 1330° C., preferably at most 1320° C. Some advantageous variants can have processing temperatures of at most 1310° C., or at most 1300° C., or even less than 1300° C. The processing temperature Va is determined so that the viscosity of the melt is at least 10 4 Homogeneity is the temperature at which the thermal conductivity of a glass-ceramic material is increased by 100% in dPa·s. Homogeneity refers in particular to the uniformity of the CTE of the glass-ceramic over a large volume as well as the low number and preferably absence of inclusions such as bubbles or particles. This is a quality characteristic of glass-ceramics and a prerequisite for their use in precision components, especially in very large precision components.
[0064] The processing temperature is determined by the composition of the glass-ceramic. In particular, the glass network former SiO2 is considered to be the determining component for increasing the viscosity and therefore the processing temperature, so the maximum SiO2 content should be selected in accordance with the above-mentioned regulations.
[0065] CTE The glass ceramic according to the invention is zero-expansion (see Table 1), i.e. the average coefficient of thermal expansion CTE in the range 0-50° C. is at most 0±0.1×10 -6 / K. In some advantageous variants, the average CTE in the range of 0 to 50° C. is at most 0±0.05×10 -6 For certain applications, the average CTE over a wider temperature range, e.g., from -30°C to +70°C, preferably from -40°C to +80°C, is at most 0±0.1×10 -6 / K, i.e., zero-expansion.
[0066] To determine the CTE-T curves of the glass ceramics and precision components according to the present invention and comparative examples, first, the differential CTE (T) is determined. The differential CTE (T) is determined as a function of temperature. The CTE is defined by the following equation (1):
number
[0067] To produce a Δl / l0-T curve, or expansion curve, or plot of the change in length Δl / l0 of a test piece (glass ceramic or precision part) versus temperature, the change in length l0 at initial temperature t0 is taken as the change in length l at temperature t. t The change in the temperature dependence of the length of the specimen up to 100° C. can be measured. In this case, a small temperature interval, for example 5° C., 3° C. or 1° C., is preferably selected to determine the measurement points. Such measurements can be carried out, for example, by dilatometry, interferometry, for example the Fabry-Perot method, i.e. evaluation of the shift of the resonance peak of a laser beam coupled to the material, or other suitable methods. In the present invention, the dilatometry method was selected to measure the CTE in the temperature interval 1° C. for rod-shaped samples of the specimen with a length of 100 mm and a diameter of 6 mm. The selected CTE measurement method preferably has an accuracy of at least ±0.05 ppm / K, preferably at least ±0.03 ppm / K. However, it will be appreciated that it is also possible to measure the CTE by a method with an accuracy of at least ±0.01 ppm / K, preferably at least ±0.005 ppm / K, or according to some embodiments even at least ±0.003 ppm / K, or at least ±0.001 ppm / K.
[0068] From the Δl / l0-T curve, the average CTE in a given temperature interval, for example, a temperature range of 0°C to 50°C, can be calculated.
[0069] By deriving the Δl / l0-T curve, the CTE-T curve is obtained. From the CTE-T curve, the zero crossings, the slope of the CTE-T curve within the temperature interval can be determined. The CTE-T curve can determine the occurrence and location of the advantageous CTE plateaus formed in some variants (see below and Figures 20 and 21).
[0070] Advantageous embodiments of precision components comprising the glass ceramic according to the invention (especially in the form of a matrix) exhibit a high CTE uniformity. The value of the CTE uniformity (English: total spatial variation of CTE) is here understood to be the so-called peak-to-valley value, i.e. the difference between the highest and lowest CTE values of the samples taken from the precision component. The CTE uniformity therefore does not refer to the CTE of the material of the component, but to the spatial variation of the CTE over the entire part or precision component. To determine the CTE uniformity, a number of samples are taken from the precision component at different positions and the CTE value is determined for each of them. This value is given in ppb / K, where 1 ppb / K=0.001×10 -6 / K. The CTE uniformity, i.e. the spatial variation of the CTE, is advantageously at most 5 ppb / K, preferably at most 4 ppb / K, most preferably at most 3 ppb / K across the precision component. Methods for determining the CTE uniformity and strategies for achieving it are described in WO 2015 / 124710, the disclosure of which is incorporated herein in its entirety.
[0071] Thermal Hysteresis In the present invention, the glass-ceramic is hysteresis-free since it exhibits a thermal hysteresis of <0.1 ppm at least in the temperature range of 10° C. to 35° C. (see FIGS. 10 and 11). Thus, at any temperature in the temperature interval of 10° C. to 35° C., the glass-ceramic after being subjected to a temperature change exhibits an isothermal length change at a subsequent constant temperature of less than 0.1 ppm.
[0072] In an advantageous embodiment, this hysteresis-free property exists in a temperature range of at least 5 to 35°C, preferably at least 5 to 45°C, preferably at least >0°C to 45°C, preferably at least -5°C to 50°C. Particularly preferred is a wider temperature range, such that the material or component is also suitable for use at temperatures up to at least 100°C, advantageously even above. Particularly preferred is a wider temperature range for the hysteresis-free property. Preferred use temperatures are in the range of -60 to 100°C, more preferably -40°C to +80°C. A particular variant of the invention is suitable for use at use temperatures T, for example in the range of 5°C to 20°C. A , or operating temperatures T of 22°C, 40°C, 60°C, 80°C, and 100°C A The present invention relates to glass ceramics and precision components at temperatures up to 1000° C., which are preferably hysteresis-free even at these temperatures.
[0073] For the glass ceramics and precision parts according to the invention as well as for comparative examples, the thermal hysteresis was measured on rod-shaped samples (i.e. samples of precision parts or samples of glass ceramics) with a length of 100 mm and a diameter of 6 mm in a temperature interval of 1° C. using a precision dilatometer capable of measuring the CTE with a reproducibility of ±0.001 ppm / K, ±0.003 ppm / K (absolute) according to the method and the device structure disclosed in DE 102015113548 A1, the disclosure content of which is incorporated herein in its entirety. For each tested sample, cooling was performed from 50° C. to −10° C. at a cooling rate of 36 K / h and the length change Δl / l0 was measured as a function of temperature. After an isothermal hold of 5 hours at −10° C., the samples were heated to 50° C. at a heating rate of 36 K / h and the length change Δl / l0 was recorded as a function of temperature. The thermal hysteresis behavior of the test specimens is studied at -5°C, 0°C, 5°C, 10°C, 22°C, 35°C and 40°C. These points are representative of the temperature range from -10°C to 50°C, since the hysteresis in the aforementioned temperature intervals decreases with increasing temperature. Thus, samples that are hysteresis-free at 22°C and 35°C do not show hysteresis even in the range up to 50°C.
[0074] To determine the thermal hysteresis at 10°C, the sample was heated and cooled at a rate of 36 K / h in the range of -10°C to 50°C, and the individual measurements of the length change were recorded for five temperatures, 8°C, 9°C, 10°C, 11°C, and 12°C, i.e., two temperature points above 10°C and two below 10°C. The average value was calculated from the differences between the measurements of the heating curve and the cooling curve at these five measurement points, and shown in the table in units of ppm as "Hyst.@10°C."
[0075] Accordingly, to determine the thermal hysteresis at 35°C, the individual measurements of the length change were recorded for five temperatures, 33°C, 34°C, 35°C, 36°C, and 37°C, when the sample was heated and cooled at a rate of 36 K / h in the range of -10°C to 50°C, i.e., the individual measurements of the length change at two temperature points above 35°C and below 35°C. The average value was calculated from the difference between the measurements of the heating curve and the cooling curve at these five measurement points, and shown in the table in units of [ppm] as "Hyst.@35°C."
[0076] The same procedure was followed for the other temperature points mentioned above.
[0077] Figures 2 to 11 show the thermal hysteresis curves of the glass-ceramics according to the invention (Figures 10 and 11) and of the known glass-ceramics (Figures 2 to 9). For ease of comparison, an interval of 6 ppm was always chosen on the Y-axis for the illustrations.
[0078] 2 to 8 show thermal hysteresis curves of known materials used in precision components. The cooling curves (dashed lines) and heating curves (dotted lines), respectively, are clearly spaced apart, i.e. extend clearly apart, from each other, especially at low temperatures. At 10°C, this separation is more than 0.1 ppm, and in some comparative examples, up to about 1 ppm. That is to say, the materials and precision components produced therefrom exhibit significant thermal hysteresis at least in the temperature range of interest, from 10°C to 35°C.
[0079] The tested LAS glass ceramics shown in Figures 2 to 5 (Comparative Example 7, Comparative Example 9, and Comparative Example 10 in Table 2), all containing MgO and ZnO, exhibit thermal hysteresis over a wide range within the temperature interval from 10 ° C to 35 ° C. Figures 6 and 7 show the hysteresis curves of the LAS glass ceramics without MgO but containing ZnO (Comparative Example 8 and Comparative Example 14 in Table 2). It can be seen that for both materials, the thermal hysteresis increases strongly below 15 ° C. Figure 8 shows the hysteresis curve of the LAS glass ceramic without ZnO but containing MgO (Comparative Example 15 in Table 2). It can be seen that this material also exhibits a strong increase in thermal hysteresis below 15 ° C. As can be seen from Figure 9, this known material (Comparative Example 1 in Table 2) does not exhibit thermal hysteresis, but the steep curve graph indicates that it is not a zero expansion material. The average CTE here is -0.24 ppm / K.
[0080] The LAS glass ceramics and precision components according to the invention have a very low content of MgO and / or ZnO or preferably are free of MgO and ZnO. As can be seen from Fig. 10 and Fig. 11, the heating and cooling curves overlap at least in the temperature range from 10°C to 35°C, i.e. the glass ceramics are hysteresis-free. However, these materials are not only hysteresis-free in the range from 10°C to 35°C, but also at least in the range from 5°C to 35°C or 5°C to 45°C, preferably at least in the range from >0°C to 45°C. Example 7 in Fig. 11 is also hysteresis-free at least in the temperature range from -5°C to 50°C.
[0081] Further expansion properties Advantageous embodiments of the present invention have further advantageous expansion features: To describe the expansion behavior of a test specimen (glass ceramic or precision component), a TCL value is often given, where TCL stands for "Total Change of Length". In the present invention, TCL values in the temperature range between 0°C and 50°C are given. This TCL value is determined from the normalized Δl / l0-T curve (also referred to as dl / l0-T curve in the figures) of each test specimen, where "normalized" means that the length change at 0°C is 0 ppm. The Δl / l0-T curve for determining the TCL is generated according to the same method as described above for the determination of CTE in the present invention.
[0082] The TCL value is the distance between the highest and lowest dl / l0 values in the temperature range:
number
[0083] Figures 14 to 17 show expansion curves of known materials from which the dl / l0 maximum and dl / l0 minimum values can be read off to calculate the TCL values (see also below). Each of these expansion curves shows a curved progression in the temperature range 0°C to 50°C.
[0084] In contrast to this, the glass ceramic and precision component according to the invention are advantageously characterized by a flat progression of the expansion curve in the temperature range from 0° C. to 50° C. (see FIGS. 12 and 13). In some advantageous variants, depending on the field of application of the component, a flat progression of the expansion curve may also be desirable in other temperature ranges, in particular in the ranges (20;40), (20;70) and / or (−10;30).
[0085] As an indicator of how far the course of the thermal expansion curve deviates from a simple linear course, in an advantageous embodiment of the invention a parameter F is introduced as an indicator of the flatness of the expansion curve, which allows a classification of CTE graphs:
number
[0086] The parameter F is calculated by taking the quotient of the TCL(0;50) value (in ppm) (see above) and the expansion difference between the temperature points 0°C and 50°C (in ppm). The expansion curve is normalized so that the length change at 0°C is 0 ppm, as defined for the determination of the TCL, so that the "expansion difference between the temperature points 0°C and 50°C" corresponds to the "expansion at 50°C" as shown in the table. The expansion at 50°C is used to calculate the parameter F.
[0087] Here, it is advantageous if, for each material or component, the parameter F is <1.2, preferably <1.1 and preferably at most 1.05. The closer the parameter F is to 1, the flatter the expansion curve will be.
[0088] In Figures 12, 13 and 18 it can be seen that the advantageous embodiment of the LAS glass ceramic has a flat progression of the expansion curve (here F=1) both in the temperature range 0° C. to 50° C. and in the wider temperature range −30° C. to 70° C. In contrast, it can be seen from Figures 14 to 17 and 19 that the known material shows a much steeper and more curved progression of the expansion curve in said temperature range.
[0089] FIG. 12 shows an exemplary expansion curve of an advantageous glass ceramic based on an advantageous ceramization of composition example 6. For illustration purposes, a section of 1.6 ppm was selected on the Y-axis. The highest expansion value (dl / l0max.) is at +50° C. (dl / l0 is +0.57 ppm, i.e. |0.57 ppm|), and the lowest expansion value (dl / l0min.) is 0 ppm. The expansion difference between the temperature points 0° C. and 50° C., which corresponds to the amount of "expansion at 50° C.", is 0.57 ppm. From this, the parameter F of this material is calculated as follows: F (example 6 of table 1)=0.57 ppm / 0.57 ppm=1.
[0090] FIG. 13 shows a further advantageous example (a composition according to example 7 of table 1), in which the parameter F is also equal to 1.
[0091] Thus, advantageous glass ceramics and precision components of the invention, for example, exhibit a very flat progression of their expansion curves in the temperature range from 0° C. to 50° C., i.e. they are not only zero-expansion in said temperature range, but also have a small variation in the change in linear expansion and thus in differential CTE in this range. As can be seen in FIG. 18, advantageous embodiments of the invention also exhibit a flat progression of their expansion curves over an even wider temperature range (here exemplarily from −30° C. to +70° C.). See in comparison the much steeper progression of the expansion curves of known materials for the same temperature range in FIG. 19. The expansion behavior can also be considered in other selected temperature ranges, in particular (−10;30), (20;40), (20,70), which are further described below.
[0092] In comparison with preferred embodiments of the glass ceramic and the precision component, Figures 14 to 17 show the expansion behavior of known materials and precision components manufactured therefrom, from which the parameter F can be calculated, respectively. The expansion behavior of the materials or precision components shown in Figures 14 to 17 and 19 was measured with the same dilatometer under conditions comparable to the expansion behavior of the preferred embodiments of the glass ceramic shown in Figures 12, 13 and 18. Overall, it can be seen that the known materials have curved progressions of the expansion curves.
[0093] FIG. 14 shows the expansion curve of commercially available titanium-doped quartz glass. Thus, the sum of the expansion value at +50°C (dl / l0max. is +0.73ppm, i.e. |0.73ppm|) and the expansion value at 14°C (dl / l0min. is -0.19ppm, i.e. |0.19ppm|) gives a TCL(0;50) value of about 0.92ppm. The expansion difference between the temperature points 0°C and 50°C, which corresponds to the amount of "expansion at 50°C", is 0.73ppm. From this, the parameter F of this material is calculated as follows: F(titanium-doped SiO2)=0.92ppm / 0.73ppm=1.26.
[0094] Correspondingly, the parameter F (see FIG. 15) for the known LAS glass-ceramic or its corresponding precision component is calculated as follows: F(known LAS glass-ceramic)=1.19 ppm / 0.11 ppm=10.82.
[0095] Correspondingly, the parameter F (see FIG. 16) for a known cordierite-glass-ceramic or a corresponding precision component is calculated as follows: F(known cordierite-glass-ceramic)=2.25 ppm / 0.25 ppm=9.
[0096] Correspondingly, the parameter F (see FIG. 17) of the known sintered cordierite ceramic or its corresponding precision component is calculated as follows: F(known sintered cordierite ceramic)=4.2 ppm / 2.71 ppm=1.55.
[0097] Glass ceramics with a flat progression of the expansion curve are highly advantageous, since not only can the precision components be optimized for the subsequent use temperature, but also show a low thermal expansion for higher and / or lower temperature loads, for example during production. Precision components for microlithography, EUV microlithography (also abbreviated as "EUV lithography" or "EUVL") and metrology are usually used in standard cleanroom conditions, in particular at room temperature of 22°C. The CTE can be adapted to this use temperature. However, such components are subjected to various process steps, such as, for example, coating with metal layers, cleaning, structuring and / or exposure processes, during which higher or possibly lower temperatures may be present than the temperature during subsequent use in the cleanroom. Advantageous glass ceramics and precision components produced therefrom, which have a parameter F of less than 1.2 and thus have an optimal zero expansion not only at the use temperature, but also possibly at higher and / or lower temperatures during production, are therefore highly advantageous. Properties such as hysteresis-freeness and a parameter F<1.2 are particularly advantageous if the precision components or glass-ceramics are used in EUV lithography, i.e. for example if the precision components are EUVL mirrors or EUVL mask blanks or corresponding substrates for these, since in EUV lithography in particular the mirrors or masks are heated very non-uniformly in the point-wise or beam direction due to the high-energy radiation. In these conditions of use, it is advantageous for the precision components or glass-ceramics to have a small slope of the CTE-T curve in the temperature range around the use temperature (see below).
[0098] Advantageous glass ceramics and precision components, which are even better optimized for the latter use temperatures of 20 or 22°C, are characterized in that the relative change in length (dl / l0) in the temperature range from 20°C to 30°C is ≦|0.10|ppm, preferably ≦|0.09|ppm, particularly preferably ≦|0.08|ppm, and very particularly preferably ≦|0.07|ppm and / or the relative change in length (dl / l0) in the temperature range from 20°C to 35°C is ≦|0.17|ppm, preferably ≦|0.15|ppm, particularly preferably ≦|0.13|ppm, and very particularly preferably ≦|0.11|ppm. Alternatively or additionally, such optimized glass ceramics and precision components can be characterized by a relative change in length (dl / l0) in the temperature range from 20° C. to 40° C. of ≦|0.30| ppm, preferably ≦|0.25| ppm, particularly preferably ≦|0.20| ppm, and especially preferably ≦|0.15| ppm. The characteristics of the relative change in length for the different temperature intervals can preferably be read off from the dl / l0 curves in FIGS. 12 to 19. When referring to the relative change in length (dl / l0), these data naturally refer to the amount of the respective value.
[0099] Zero-expansion, hysteresis-free materials exhibiting such advantageous expansion behavior are particularly suitable for use as substrates for EUVL mirrors or as EUVL mirrors which are heated differently in light and shadow areas during operation, for example due to the respective exposure mask. Due to the small relative changes in length as described above, EUVL mirrors made from the advantageous glass-ceramics have smaller local gradients (local tilts) in the topography of the mirror surface than EUVL mirrors made from known materials. The same is true for EUVL mask blanks or EUVL masks or EUVL photomasks.
[0100] In particular in glass-ceramics which exhibit a very flat progression of the expansion curve, which fluctuates in the vicinity or around 0 ppm in the temperature range in question and which results in an overall favourable expansion behaviour, it is advantageous, alternatively or additionally possible to introduce a further indicator of the flatness of the expansion curve into the parameter F, the expansion curve not being taken into account in the temperature range (0;50) but in other temperature intervals (Ti), preferably in the temperature ranges (20;40), (20;70) and / or (-10;30), which allows a better classification of the expansion behaviour in relation to the subsequent field of application.
[0101] Alternative parameter f T.i. has units (ppm / K),
number
[0102] TCL (T.i.) The value is the difference between the maximum and minimum dl / l0 values in the respective temperature ranges (Ti), where the expansion curve is (T.i.) For the determination of, it is also normalized so that the length change at 0°C is 0 ppm according to the definition. So, for example,
number
[0103] Alternative parameter f T.i. According to equation (4), TCL (T.i.)It is calculated by taking the quotient of the value [unit: ppm] (see above) and the width of the temperature interval (Ti) given in [K] taking into account the expansion difference. The width of the relevant temperature interval from 20°C to 40°C is 20K. On the other hand, if the progression of the expansion curve in the interval Ti = (20; 70) or (-10; 30) is taken into account, the divisors in formula (4) are 50K and 40K, respectively.
[0104] In an advantageous embodiment, the glass ceramic has an alternative parameter f (20;40) <0.024ppm / K, and / or alternative parameter f (20;70) <0.039ppm / K, and / or alternative parameter f (-10;30) <0.015 ppm / K.
[0105] Glass-ceramics with a very flat progression of the expansion curve are very advantageous since they allow the optimization of precision components not only for the subsequent use temperature but also for loading at higher and / or lower temperatures, for example, and can be used to calculate the alternative parameter f T.i. is suitable for determining suitable materials according to the specifications required for a particular part application, and for providing corresponding precision parts. Specific precision parts and their applications are further described and included below.
[0106] According to an advantageous embodiment of the glass ceramic or a component manufactured therefrom, the alternative parameter f (20;40) It may be advantageous for the expansion behavior in the temperature range (20;40) to be <0.024 ppm / K, preferably <0.020 ppm / K, preferably <0.015 ppm / K. Hysteresis-free zero-expansion components exhibiting an expansion behavior in such a temperature range (20;40) can be particularly well used as precision components for microlithography at room temperature and for EUV microlithography. An example of such an advantageous glass-ceramic is shown in FIG. 27.
[0107] According to an advantageous embodiment of the glass ceramic or a component manufactured therefrom, the alternative parameter f (20;70)It may be advantageous if the thermal expansion coefficient is <0.039 ppm / K, preferably <0.035 ppm / K, preferably <0.030 ppm / K, preferably <0.025 ppm / K, preferably <0.020 ppm / K. Hysteresis-free zero-expansion components with an expansion behavior in such a temperature range (20;70) can also be particularly well used as precision components for microlithography and EUV microlithography. It is particularly advantageous if the components also exhibit a low thermal expansion under higher temperature loads, which may occur, for example, locally or widely during the manufacture of the precision components but also during operation. Further details of the temperature loads occurring in EUVL precision components have already been described above with respect to the parameter F and are referred to here to avoid repetition. An example of such an advantageous glass-ceramic is shown in FIG. 29.
[0108] According to an advantageous embodiment of the glass ceramic or a component manufactured therefrom, the alternative parameter f (-10;30) It may be advantageous if the expansion coefficient is <0.015 ppm / K, preferably <0.013 ppm / K, preferably <0.011 ppm / K. Hysteresis-free zero-expansion components with an expansion behavior in such a temperature range (-10;30) can be particularly well used as precision components, in particular as mirror substrates for applications where temperatures below room temperature may also occur, for example in astronomy or Earth observation from outer space. Corresponding components are described below. Examples of such advantageous glass ceramics are shown in Figs. 28 and 30.
[0109] A particularly advantageous embodiment of the glass ceramic or a component manufactured therefrom is characterized in that the alternative parameter f (T.i.) At least two of the above have suitable expansion curves.
[0110] A particularly advantageous embodiment of the glass ceramic or a component manufactured therefrom is characterized in that the parameter F and at least one alternative parameter f (T.i.) has an expansion curve where
[0111] 20 and 21 show that advantageous embodiments of LAS glass ceramics and precision components have a CTE plateau. Glass ceramics exhibiting a plateau, i.e. optimized zero expansion over a wide temperature range, offer the same advantages as already mentioned above in relation to the flat progression of the expansion curve and the parameter F.
[0112] When the differential CTE has a plateau near 0 ppm / K, i.e., the temperature interval T P Advantageously, the differential CTE at is less than 0±0.025 ppm / K. The temperature interval of the CTE plateau is defined as T P Advantageously, the temperature interval T has a width of at least 40 K. P The differential CTE at may be less than 0±0.015 ppm / K.
[0113] A CTE plateau is therefore understood to be the range spanning the portion of the CTE-T curve where the differential CTE does not exceed a value of 0±0.025 ppm / K, preferably 0±0.015 ppm / K, more preferably 0±0.010 ppm / K, even more preferably 0±0.005 ppm / K, i.e. a CTE around 0 ppb / K.
[0114] Advantageously, the temperature interval T has a width of at least 40 K. P The differential CTE at may be less than 0±0.015 ppm / K, i.e. 0±15 ppb / K. In a preferred embodiment, a CTE plateau of 0±0.01 ppm / K, i.e. 0±10 ppb / K, may be formed over a temperature interval of at least 50 K. In FIG. 25, the average curve further shows a CTE plateau of 0±0.005 ppm / K, i.e. 0±5 ppb / K, from 7 to 50° C., i.e. over a range of more than 40 K.
[0115] Temperature interval T P It may be advantageous if the temperature is in the range of -10 to +100°C, preferably 0 to 80°C.
[0116] The position of the CTE plateau of the glass ceramic is determined by the operating temperature T A The preferred operating temperature T A is in the range of -60°C to +100°C, more preferably -40°C to +80°C. Particular variations of the invention are suitable for use at temperatures T of 0°C, 5°C, 10°C, 22°C, 40°C, 60°C, 80°C and 100°C. A The present invention relates to precision components and glass ceramics in the temperature range T P Curve ranges with low deviations in the differential CTE at may also exist in the temperature ranges of [-10;100];[0;80], [0;30°C], [10;40°C], [20;50°C], [30;60°C], [40;70°C] and / or [50;80°C].
[0117] According to an advantageous embodiment of the invention, the CTE-T curve of the glass ceramic or the precision component has a low slope, in particular a slope of at most 0±2.5 ppb / K, in a temperature range having a width of at least 30 K, preferably at least 40 K, more preferably at least 50 K. 2 , advantageously at most 0±2 ppb / K 2 , advantageously at most 0±1.5 ppb / K 2 , preferably at most 0±1 ppb / K 2 , preferably at most 0±0.8 ppb / K 2 , and even at most 0±0.5 ppb / K according to certain variants. 2 The curve has at least one curved portion where
[0118] The temperature range with a small slope is the operating temperature T A The preferred operating temperature T A is in the range of -60°C to +100°C, more preferably -40°C to +80°C. Particular variations of the invention are suitable for use at temperatures T of 0°C, 5°C, 10°C, 22°C, 40°C, 60°C, 80°C and 100°C. AThe temperature intervals with a small slope may also be present in the temperature ranges [-10; 100]; [0; 80], [0; 30 °C], [10; 40 °C], [20; 50 °C], [30; 60 °C], [40; 70 °C] and / or [50; 80 °C].
[0119] FIG. 22 shows the slope of the CTE-T curve in the temperature range of 0° C. to 45° C. for the advantageous glass ceramic or precision component based on the composition of Example 6 in Table 1. The slope of the CTE is 0±2.5 ppb / K over the entire temperature range. 2 and 0±1.5 ppb / K for at least a 30K wide interval. 2 is less than.
[0120] In FIG. 23, the CTE slope of the advantageous glass ceramic and precision component corresponding to Composition Example 7 in Table 1 is 0±1.0 ppb / K over the entire temperature range of 0° C. to 40° C. with a width of at least 40 K. 2 and 0±0.5 ppb / K for at least a 30K wide interval. 2 It can be seen that it is less than
[0121] In FIG. 26, the CTE slope of the advantageous glass ceramic and precision component corresponding to Example 17 in Table 1 is 0±1.0 ppb / K over the entire temperature range of 0° C. to 45° C. with a width of at least 45 K. 2 and 0±0.5 ppb / K for at least a 30K wide interval. 2 It can be seen that it is less than
[0122] Glass ceramics and precision components that exhibit such expansion behavior are particularly well suited for EUV lithography applications (e.g. as mirrors or substrates for mirrors or masks or mask blanks), since in this field increasingly high demands are made on materials and precision components used in optical components with regard to extremely low thermal expansion, zero crossings of the CTE-T curve near the application temperature, and in particular low slopes of the CTE-T curve. In the present invention, advantageous embodiments of the glass ceramics or precision components have a very flat CTE profile, where the graph shows both a zero crossing and a very low CTE slope, and possibly even a very flat plateau.
[0123] The low slope feature can be present with or without the formation of a favorable CTE plateau.
[0124] Figures 24 and 25 show how the CTE graph can be adapted to different use temperatures by varying the ceramization temperature and / or the ceramization time. As can be seen from Figure 24, by increasing the ceramization temperature by 10 K, the zero crossing of the CTE-T curve can be shifted, for example, to a value of 12°C to 22°C. Instead of increasing the ceramization temperature, the ceramization time can be correspondingly extended. Figure 25 illustrates that, for example, by increasing the ceramization temperature by 5 to 10 K, the very flat progression of the CTE-T curve can be increased. Also, instead of increasing the ceramization temperature, the ceramization time can be correspondingly extended.
[0125] The preferred glass ceramics and precision components further have a good internal quality. Preferably, the preferred glass ceramics and precision components have a thickness of 100 cm 3 The number of inclusions per particle is at most 5, more preferably at most 3, most preferably at most 1. According to the invention, inclusions are understood to mean both bubbles and crystallites with a diameter of more than 0.3 mm.
[0126] According to a variant of the invention, the diameter or side length is at most 800 mm and the thickness at most 100 mm, 3 The present invention provides a precision component having at most 5, preferably at most 3, and more preferably at most 1 inclusion having a diameter of more than 0.03 mm per unit area.
[0127] In addition to the number of inclusions, the maximum diameter of the detected inclusions is also an indicator of the internal quality. The maximum diameter of the individual inclusions in the total volume of precision parts with a diameter of less than 500 mm is preferably at most 0.6 mm, and in the volumes important for use, for example near the surface, it is preferably at most 0.4 mm. The maximum diameter of the individual inclusions in glass-ceramic parts with a diameter of 500 mm to less than 2 m is preferably at most 3 mm, and in the volumes important for use, for example near the surface, it is preferably at most 1 mm.
[0128] The invention further relates to the use of the glass ceramic according to the invention in precision components, for example the glass ceramic can form the substrate of a precision component.
[0129] The invention further relates to the use of the LAS glass ceramics according to the invention in precision components, in particular for use in metrology, spectroscopy, measurement engineering, lithography, astronomy or Earth observation from outer space, for example as mirrors or mirror supports for segmented or monolithic astronomical telescopes or as light or ultralight mirror substrates, for example for space-based telescopes or as high-precision structural components, for example for distance measurements in outer space or optical components for Earth observation, as precision components such as standards, precision measuring instruments, reference plates for interferometers for precision metrology, for example as mechanical precision components, for example ring laser gyroscopes, clockwork springs, as mirrors and prisms, for example in LCD lithography and as mask holders, wafer tables, reference plates, reference frames and grid plates, for example in microlithography and EUV (Extreme UV) microlithography, and also as mirrors or mirror substrates and / or photomask substrates or photomask blanks or reticle mask blanks in EUV microlithography.
[0130] The glass ceramic according to the invention makes it possible to produce precision components of different sizes.
[0131] An embodiment relates to precision parts of smaller dimensions, in particular in the (right)angle or on rounded faces, with side lengths (width and / or depth) of at least 100 mm and / or up to 1500 mm diameter and / or less than 50 mm, preferably less than 10 mm and / or at least 1 mm, more preferably at least 2 mm thickness. Such precision parts can be used, for example, for microlithography and EUV lithography.
[0132] Another embodiment relates to precision components with very small dimensions, in particular side lengths (widths and / or depths) or diameters and / or thicknesses of a few mm (for example at most 20 mm, or at most 10 mm, or at most 5 mm, or at most 2 mm, or at most 1 mm) to a few tenths of a mm (for example at most 0.7 mm, or at most 0.5 mm). Such precision components can be used, for example, as spacers in interferometers or as components of ultrastable clocks in quantum engineering.
[0133] However, it is also possible to manufacture very large precision parts. Thus, one embodiment of the present invention relates to large volume parts, which in the present application means parts having a weight of at least 300 kg, preferably at least 400 kg, preferably at least 500 kg, preferably at least 1 t, more preferably at least 2 t, according to a variant of the invention at least 5 t, or, if (right)angled, a side length (width and / or depth) of at least 0.5 m, more preferably at least 1 m, and a thickness (height) of at least 50 mm, preferably at least 100 mm, or, if rounded, a diameter of at least 0.5 m, more preferably at least 1 m, more preferably at least 1.5 m, and / or a thickness (height) of at least 50 mm, preferably at least 100 mm. In a particular embodiment of the present invention, this may be even larger parts, for example with a diameter of at least 3 m or at least 4 m or more. According to a variant, the present invention also relates to rectangular parts, preferably with at least one surface having a thickness of at least 1 m. 2 , preferably at least 1.2 m 2 , more preferably at least 1.4 m 2 This also applies to rectangular parts with an area of 0.01 mm or less. Typically, large volume parts are manufactured whose base area is much larger than their height. However, large volume parts with shapes closer to cubes or spheres can also be manufactured.
[0134] The precision components can be, for example, optical components, so-called normal incidence mirrors, i.e. mirrors operating close to normal incidence of radiation, or so-called grazing incidence mirrors, i.e. mirrors operating at grazing incidence of radiation. Such mirrors contain, in addition to a substrate, a coating that reflects the incident light. In particular, in the case of mirrors for X-rays, the reflective coating is a multilayer system or multilayer, for example with a number of layers with a high reflectivity in the X-ray range at incidence without a grazing angle. Preferably, such a multilayer system of a normal incidence mirror contains, for example, 40 to 200 layers of alternating material pairs, one of which is Mo / Si, Mo / Bi, Ru / Si and / or MoRu / Be.
[0135] In particular, the optical element according to the invention may be an X-ray optical element, i.e. an optical element for use in combination with X-rays, in particular soft X-rays or EUV radiation, in particular a reticle mask or photomask operating in reflection for EUV microlithography. Advantageously, it may be a mask blank. More advantageously, the precision component can be used as a mirror for EUV lithography or as a substrate for a mirror in EUV lithography.
[0136] Furthermore, the precision component according to the invention can be a component, in particular a mirror for astronomy, where such an astronomy component can be used both on the ground and in space.High-precision structural components, for example for distance measurement in space, are further advantageous fields of application.
[0137] The precision part according to the present invention may be a lightweight structure. The part according to the present invention may further include a lightweight structure. That is, a cavity is provided in a part of the part to reduce its weight. Preferably, the weight of the part is reduced by at least 80%, more preferably at least 90%, by the lightweight processing compared to the unprocessed part.
[0138] The subject of the invention is also a precision component comprising a LAS glass ceramic according to the invention, the details of which have already been mentioned above with respect to the glass ceramic and its use in precision components, the disclosure of which is incorporated in its entirety by reference for the description of the precision component.
[0139] It is understood that the features of the invention mentioned above and those to be described hereinafter can be used not only in the respective combinations shown but also in other combinations without departing from the scope of the invention.
[0140] Working Example Tables 1 and 2 show the compositions of examples of glass ceramics according to the present invention and comparative examples, as well as their properties.
[0141] The compositions shown in Table 1 were melted by conventional manufacturing methods from commercially available raw materials such as oxides, carbonates, and nitrates. The green glasses produced according to Table 1 were first ceramized at the maximum temperatures shown for the times shown.
[0142] The production of glass-ceramics for precision components, in particular large precision components, is described, for example, in WO 2015 / 124710.
[0143] Table 1 shows 23 examples of the invention which are zero expansion and hysteresis-free at least in the temperature range from 10°C to 35°C. Examples 6, 18, 19 and 20 show no thermal hysteresis up to about 0°C, and Examples 11, 17 and 23 show no thermal hysteresis up to -5°C. Examples 7, 12, 14, 15 and 22 are hysteresis-free over the entire temperature range from -5°C to 45°C. Furthermore, the parameter F<1.2, i.e. the progression of the expansion curve in the temperature range from 0°C to 50°C is advantageously flat in all examples. Furthermore, the processing temperatures in these examples are ≦1330°C, which allows the production of highly homogeneous glass ceramics in industrial production plants. The processing temperatures shown in Tables 1 and 2 were determined according to DIN ISO 7884-1 (2014 - Source: Schott Techn. Glas-Katalog).
[0144] In Example 5, after ceramization for 2.5 days at a maximum temperature of 780°C, the average CTE was determined for further temperature intervals, giving the following results: CTE(20;300°C): -0.17 ppm / K, CTE(20;500°C): -0.02 ppm / K, CTE(20;700°C): 0.17 ppm / K.
[0145] In Example 7, the average CTE was determined over the temperature range of 19° C. to 25° C., and the following results were obtained: In Example 7, the CTE (19;25) was −1.7 ppb / K.
[0146] Table 2 shows comparative examples. Comparative Example 1, Comparative Example 2, Comparative Example 5, and Comparative Example 6 do not contain MgO or ZnO, but have an average CTE(0;50) of 0±0.1×10 -6 / K, i.e. these comparative examples are not zero expansion. Furthermore, the processing temperatures of Comparative Example 1 and Comparative Example 2 are above 1330° C. The viscosity of these materials is so high that highly homogeneous parts cannot be manufactured from these materials in industrial production plants.
[0147] Comparative Examples 7 to 16 all contain MgO and / or ZnO, and most of them are zero expansion. However, these comparative examples show thermal hysteresis well above 0.1 ppm at least in the temperature range of 10°C to 35°C. At room temperature, i.e., 22°C, this group of comparative examples shows thermal hysteresis except for Comparative Examples 14 and 16. Furthermore, although Comparative Example 9 is zero expansion, it shows an undesirably steep transition of the expansion curve in the temperature range of 0°C to 50°C, which is evident from the high value of parameter F.
[0148] Blank entries in the composition data tables below mean that those ingredients are not intentionally added or included.
[0149] Table 3 shows the calculated surrogate parameters f for different temperature intervals for some advantageous embodiments of the present invention and comparative examples. (T.i.) , from which it can be seen that the expansion curves of the Examples show a flatter progression than the Comparative Examples in the indicated temperature ranges.
[0150] It will be clear to a person skilled in the art that depending on the application temperature of the glass ceramic or of the precision component containing the glass ceramic, a glass ceramic will be selected which exhibits the desired properties, in particular with regard to thermal hysteresis and / or average CTE.
[0151] [Table 3-1]
[0152] [Table 3-2]
[0153] [Table 3-3]
[0154]
Table 3-4
[0155]
Table 4-1
[0156]
Table 4-2
[0157]
Table 4-3
[0158]
Table 5
Claims
1. A LAS glass ceramic having an average coefficient of thermal expansion CTE of up to 0±0.1×10 in the range of 0° C. to 50° C. -6 / K, has a thermal hysteresis of <0.1 ppm in the temperature range of at least 10° C. to 35° C., and contains the following components (in mole % on an oxide basis): 【Table 1】 P 2 O 5 , R 2 At least one moiety selected from the group consisting of O, and RO, where R 2 O is Na 2 O and / or K 2 O and / or Cs 2 O and / or Rb 2 O, and RO may be CaO and / or BaO and / or SrO. A nucleating agent having a content of 1.5 to 6 mol %, said nucleating agent being TiO 2、 ZrO 2、 T 2 O 5 , Nb 2 O 5 , SnO 2 , MoO 3 , W.O. 3 A nucleating agent, which is at least one component selected from the group consisting of: The LAS glass ceramic.
2. The LAS glass ceramic is Al 2 O 3 and / or P 2 O 5 2. The LAS glass ceramic according to claim 1, comprising a content of 0.1 to 6 mol %, preferably 0.3 to 5 mol % of
3. 3. The LAS glass-ceramic according to claim 1 , wherein the total content of ZnO+MgO is ≦0.55 mol%, preferably ≦0.5 mol%, preferably <0.5 mol%, preferably ≦0.45 mol%, preferably ≦0.4 mol%, preferably ≦0.3 mol%, preferably ≦0.2 mol%, and / or the content of MgO is ≦0.35 mol%, preferably ≦0.3 mol%, preferably ≦0.25 mol%, preferably ≦0.2 mol%, more preferably ≦0.1 mol%, and / or the content of ZnO is ≦0.5 mol%, preferably ≦0.45 mol%, preferably ≦0.4 mol%, preferably ≦0.3 mol%, preferably ≦0.2 mol%, more preferably ≦0.1 mol%.
4. SiO 2 4. The LAS glass ceramic according to claim 1 , wherein the content of is ≦70 mol %, preferably ≦69 mol %, particularly preferably ≦68.5 mol %.
5. 5. The LAS glass ceramic according to claim 1 , wherein the content of the sum of RO (CaO+BaO+SrO) is ≧0.1 mol%, preferably ≧0.2 mol%, advantageously ≧0.3 mol%, preferably ≧0.4 mol% and / or ≦6 mol%, preferably ≦5 mol%, advantageously ≦4.5 mol%, advantageously ≦4.0 mol%, preferably ≦3.8 mol%, preferably ≦3.5 mol%, preferably ≦3.2 mol%.
6. R 2 O(Na 2 O+K 2 O+Cs 2 O+Rb 2 6. The LAS glass ceramic according to claim 1 , wherein the total content of the elements C1, C2, C3, C4, C5, C6, C7, C8, C9, C10, C11, C12, C13, C14, C15, C16, C17, C18, C20, C21, C31, C42, C43, C54, C65, C76, C87, C98, C99, C100, C111, C122, C130, C140, C150, C161, C172, C183, C190, C224, C230, C310, C42, C43, C54, C65, C76, C87, C98, C101, C112, C124, C135, C240, C310, C42, C43, C54, C65, C76, C87, C99, C102, C113, C125, C136, C140, C230, C310, C43, C44, C55, C66, C77, C78, C99, C103, C114, C125, C135, C240, C310, C42, C43, C55, C66, C77, C99, C104, C115, C125, C136, C140, C230, C310, C43, C44, C55, C66, C77, C99, C105, C116, C126, C137, C240, C310, C43, C44, C55, C67, C78, C99, C
7. 7. The LAS glass ceramic according to claim 1, wherein the total content of nucleating agents is ≧1.5 mol%, preferably ≧2.5 mol%, advantageously ≧3 mol% and / or ≦6 mol%, advantageously ≦5 mol%, preferably ≦4.5 mol%, preferably ≦4 mol%.
8. SiO 2 Molar fraction of + (5 × Li 2 O mole fraction) ≧106, preferably SiO 2 Molar fraction of + (5 × Li 2 and / or SiO 2 Molar fraction of + (5 × Li 2 O mole fraction)≦115.5, preferably SiO 2 Molar fraction of + (5 × Li 2 8. The LAS glass ceramic according to claim 1 , wherein the following condition holds: the molar fraction of ZnO in the glass is 114.
5.
9. 9. The LAS glass ceramic according to claim 1, wherein the treatment temperature Va is at most 1330°C, preferably at most 1320°C.
10. 10. The LAS glass ceramic according to claim 1, wherein the main crystalline phase is a high quartz solid solution, the average crystallite size of the high quartz solid solution being preferably <100 nm, preferably <80 nm, preferably <70 nm, and / or the proportion of crystalline phase is less than 70 vol.-%.
11. 11. The LAS glass ceramic according to claim 1 , wherein the parameter F is <1.2, preferably <1.1, preferably at most 1.05, where F=TCL(0;50° C.) / |Expansion(0;50° C.)|.
12. Alternative parameter f (20;40) <0.024 ppm / K, and / or alternative parameter f (20;70) <0.039 ppm / K, and / or alternative parameter f (-10;30) 12. The LAS glass ceramic according to claim 1 , wherein the LAS content is <0.015 ppm / K.
13. The relative change in length (dl / l) in the temperature range of 20°C to 30°C 0 ) is ≦|0.10| ppm, preferably ≦|0.09| ppm, particularly preferably ≦|0.08| ppm, and especially preferably ≦|0.07| ppm, and / or the relative change in length (dl / l) in the temperature range from 20° C. to 35° C. 0 13. The LAS glass ceramic according to claim 1, wherein the LAS content is ≦|0.17| ppm, preferably ≦|0.15| ppm, particularly preferably ≦|0.13| ppm, and especially preferably ≦|0.11| ppm.
14. The relative change in length (dl / l) in the temperature range of 20°C to 40°C 0 14. The LAS glass ceramic according to claim 1 , wherein the LAS content is ≦|0.30| ppm, preferably ≦|0.25| ppm, particularly preferably ≦|0.20| ppm, and especially preferably ≦|0.15| ppm.
15. The CTE-T curve has a temperature range of at least 30 K and is ≦0±2.5 ppb / K. 2 , preferably ≦0±2 ppb / K 2 , preferably ≦0±1.5 ppb / K 2 , particularly preferably ≦0±1 ppb / K 2 15. The LAS glass ceramic according to claim 1 , wherein the LAS has a gradient of:
16. 16. The LAS glass ceramic according to claim 1, wherein the LAS glass ceramic exhibits a thermal hysteresis of <0.1 ppm at least in the temperature range from 5° C. to 45° C., advantageously at least in the temperature range from >0° C. to 45° C., preferably at least in the temperature range from −5° C. to 50° C.
17. 17. Use of the LAS glass ceramic according to any one of claims 1 to 16 in precision components, in particular for use in metrology, spectroscopy, measurement engineering, lithography, astronomy or Earth observation from outer space, for example as mirrors or mirror supports for segmented or monolithic astronomical telescopes or as lightweight or ultralight mirror substrates, for example for space-based telescopes or as high-precision structural components, for example for distance measurements in outer space or optical components for Earth observation, as precision components, such as standards, precision measuring instruments, reference plates for interferometers, for example as ring laser gyroscopes, mechanical precision components of clockwork springs, for example as mirrors and prisms, for example in LCD lithography, and as mask holders, wafer tables, reference plates, reference frames and grid plates, for example in microlithography and EUV microlithography, and as mirrors and / or photomask substrates or reticle mask blanks in EUV microlithography.